(untitled) (Journal of the College of Education for Women, 2019)
I’ve led an end to the Palestinian presence in the Jordan to the occurrence of a major fault line in relations between Jordan and the Palestinian on the levels of all , and as a result sought King Hussein and the initiative of the U.S. to heal the rift that solution between Jordanians , Palestinians, and the regulation of relations between the two parties announced in March 1972 for the project and unitary featuring Jordan and Palestine in the Arab kingdom united with the two countries , but that the Palestine Liberation Organization and the Palestinian resistance factions rejected by asserting that it is has the right of self-determination of the Palestinian people and no one else , and rejected by the Arab states and ( Israel ) , and led the project of Jordan to isolate Arab political to Jordan